The additional diagnostic value of NLR and PLR for CA-125 in the differential diagnosis of endometrioma and benign ovarian cysts in women of reproductive age: a retrospective case-control study - Kalem, Ziya; Şimşir, Çoşkun; Bakırarar, Batuhan; Namlı Kalem, Müberra (The European Research Journal, 2020)
Objectives: Aim of this study is to investigate the diagnostic value of neutrophil/lymphocyte ratio (NLR) and platelet/lymphocyte ratio (PLR) for cancer antigen-125 (CA-125) in a differential diagnosis of endometrioma from benign ovarian cysts. Methods: In this retrospective study, the medical data of a total of 213 patients aged < 40 years who underwent laparoscopic or laparotomic surgery for ovarian cysts between April 2015 and June 2018 were analyzed. The patients were divided into two groups, as those with endometriomas and those with other benign ovarian cysts, all which had been confirmed histopathologically. Data on age, body mass index (BMI), preoperative US findings, complete blood count analysis results, follicle-stimulating hormone (FSH) levels, and the presence of dysmenorrhea, dyspareunia and chronic pelvic pain were recorded. Results: NLR, PLR and CA-125 were increased in the patients with endometrioma, although increases in the NLR and PLR alone or combined did not contribute to the sensitivity or specificity of CA-125. Conclusions: The results of our study suggest that NLR and PLR did not contribute to the diagnostic value of CA-125 in the preoperative differential diagnosis of endometriomas or other benign ovarian cysts. In addition, CA-125 was not associated with clinical symptoms, although a relationship was identified between NLR and dysmenorrhea, and between PLR and lesion size, which may be the research focus of further studies.